The Effect of Supplementary Food in the Form of Moringa Leaf Dry Brownies on the Increasing Weight of Under-Fives with Underweight Status in Wonokerto Village Turi Sleman - Febriana Renitasari; Masini; Ayuningtyas (PT FORMOSA CENDEKIA GLOBAL, 2023)
In 2020, the percentage of underweight children under-five in Indonesia is high, which is 6.7% or a total of 779,139 children under-five. This shows that the problem of under-five malnutrition is still high both in Indonesia and the regions. This study aims to determine the effect of providing additional food in the form of dry brownies of moringa leaves on the increase in body weight of toddlers with poor nutritional status. This study used Pre-Experimental designs, One Group Pretest and Posttest with a sample of 34 underweight toddlers were intervened for 21 days. The results showed that there was an increase under-five weight between before and after being given moringa leaf brownies with a p value of 0.000 < 0.05. The conclusion is there is an effect of providing additional food in the form of dry brownies of Moringa leaves on increasing body weight in under-fives with underweight status.